Malaria vaccine: The tale of terror, triumph, tyranny, and trust - Joyeeta Talukdar,; Tryambak Srivastava,; Abhibrato Karmakar,; Kakali Purkaystha,; Sandeep Goswami,; Arun Kumar,; Dhar, Ruby; Subhradip Karmakar, (Asian Journal of Medical Sciences, 2022)
Malaria is an endemic disease in a true sense. It is an acute febrile disease caused due to the parasite Plasmodium. However, unlike COVID-19, it failed to raise an international concern or gain the scientific limelight. Most of the 200 million globally affected by malaria, half of them are from Africa. Four of the nations, Nigeria (25%), the Democratic Republic of the Congo (11%), Mozambique (5%), and Uganda (4%), account for half of the world’s malaria burden and is the leading cause of illness and death. In 2019, an estimated 5–6 million people died of malaria – most of them are young children in sub-Saharan Africa. Many of the countries affected by malaria have the lowest economic status. In the malaria-endemic region, the most vulnerable groups are young children and pregnant women. The costs of malaria are enormous to individuals, families, communities, societies, and nations. After a struggle for three decades, the much-awaited malaria vaccine, RTS, S (brand name Mosquirix), was finally launched; but it came with its controversies and allegations. This review explored the different angles of this disease, the vaccine development, and the emerging debates.